The relationship between self-regulated learning and employability skills among tvet students mediated by satisfaction with personal record building / Sarah Nadiah Rashidi - Rashidi, Sarah Nadiah (2024)
The subject of employability skills has always been on the agenda of stakeholders such as the government, universities, and employers in the industry. Changes in the employability skills needed at workplace necessitate stakeholders to discover new methods to stay relevant. Earlier literature reveals that while the technical and vocational training (TVET) primarily centralises hard skills, there is a growing demand for soft skills. A technical university presented the Personal Record Building (PRB) system as a method of developing desired employability skills. The PRB system, like ePortfolio, is primarily based on students' ability to self-regulate and record their participation and accomplishment in students' activities via a merit system. As a result, it is critical to investigate the link between students' self-regulated learning strategies, satisfaction with the PRB system, and employability skills. The aim of this research is to determine the contributing factors that influence employability skills. The objectives of this research are to examine the impact of selfregulated learning strategies (goal setting, help-seeking, and self-monitoring) and students’ satisfaction with the PRB system on employability skills, as well as to examine the role of students' satisfaction with the PRB system as a mediator in the relationship between self-regulated learning strategies and employability skills. This research used a correlational research design to identify the relationships between variables. Data was collected from 159 final-year students at a specific technical university. SPSS v26 was deployed for descriptive analysis and SmartPLS was utilised for measurement and structural model. The findings show that goal setting, self-monitoring, and help-seeking strategies have a significant influence on employability skills. It is also evident that students’ satisfaction with the PRB system is a predicting factor for employability skills. Through bootstrapping procedure, it was found that students’ satisfaction with the PRB system partially mediates the relationship between help-seeking strategy and employability skills. These findings aid universities in assessing and improving their services using the PRB system and aiding students in using self-regulated learning strategies, which consequently, developing desired employability skills. Besides increasing the number of respondents, future research is recommended to incorporate qualitative method to further confirm the structural model. Additionally, it is recommended to explore the potential moderating effects of demographic variables on the relationship between self-regulated learning and employability skills to provide valuable insights into the dynamics of these variables.